Preparation and characterization of a graphene hybridizing polyurethane damping composite - Ma Chi; Zhang WeiLin; Wang LianHui; Guo Zhuo; Jiang Yan; Shan Yi; Chen JingYi; Wang Ying; Sin Lee Tin (Science and Engineering of Composite Materials, 2022)
A graphene hybridizing polyurethane/polyethyl methacrylate (GR-PU/PEMA) damping composite was synthesized using the sequential interpenetration method. The effects of the graphene content and the microphase separation structure on the damping properties, thermal stability, and mechanical properties have been studied in detail. The dynamic mechanical analysis indicated that graphene could improve the damping peak value of PU/PEMA, and the microphase separation structure could be beneficial for broadening the damping temperature range. The damping peak (tan σ max) of PU/PEMA hybridizing with 0.5 wt% graphene reached 0.82, and the temperature range of the loss factor (tan σ ≥ 0.3) was expanded to 88.3°C. Analysis of scanning electron microscopy, transmission electron microscopy, and small-angle X-ray scattering reveals that graphene is uniformly dispersed in the polymer matrix, and the composite with interpenetrating polymer network (IPN) shows more microphase separation structures. Fourier transform infrared analysis indicated that there is strong interaction between graphene and IPN matrix. Furthermore, the addition of graphene improved the mechanical properties and thermal stability of composites.